Antecedents to Customer Loyalty in the Restaurant Industry : A Millennial Perspective - Shetty, Bhavna; Bhandary, Rakshith; Chandra, Sachin R.; Shetty, Adithya D. (Indian Journal of Marketing, 2018)
Food is an essential module of everyone’s life, not only as a tool for good health, but also to provide structure to our routine life. With a lot of options around to latch on to different segments like cafés, quick service restaurants, fine dining, and casual dining, we tried to analyze in our study the most preferred segment among millennials and the reasons behind their preferences. These preferences were tested using responsiveness, food quality, restaurant image, and customer perceived value with a mediating effect of satisfaction leading to loyalty. The conceptual model was empirically evaluated using a quantitative method to measure the research constructs. A total of 417 millennials from Karnataka were considered for the study. Probability multistage cluster sampling was used for selecting the respondents. The data were analyzed using the partial least square structural modeling (SMART PLS3) approach. The PLS - SEM mediator analysis results revealed that customer perceived value fully mediated to loyalty ; whereas, responsiveness, restaurant image, and food quality led to satisfaction. According to the multi-group analysis results, under cafes, restaurant image was the most preferred segment among the millennials.